A BIDIRECTIONAL CASCADED MULTIPHASE BOOST-BUCK CONVERTER INTERFACING ELECTRIC VEHICLE BATTERY AND DC MICROGRID - Wijanarko, Sulistyo
This paper proposes a bidirectional cascaded multiphase boost-buck converter interfacing Electric Vehicle (EV) battery and DC microgrid bus. The converter has a simple structure, capable to be operated in various levels of input and output voltages with a minimum battery side current ripple. Optimization on both sides of the converter has been done to determine the optimal number of phases and switching frequency. Output voltage and power loss analysis of the proposed converter is performed by considering the parasitic parameters of the components. Finally, experimental results using a scaled-down prototype are shown to verify the proposed analysis of the converter.